2006
DOI: 10.4161/cc.5.22.3472
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Histone H2AX on Ser 139 and Activation of ATM During Oxidative Burst in Phorbol Ester-Treated Human Leukocytes

Abstract: Oxidative burst is a defense mechanism used by specialized phagocytes such as granulocytes or monocytes to kill the invading microorganisms through generation of superoxide anions. Oxidative burst also results in DNA damage of the phagocytes. Phagocytes are terminally differentiated cells, some of very short life-span cells. We could find no reports whether oxidative burst-mediated DNA damage triggers in such cells histone H2AX-Ser139 phosphorylation and activation of Ataxia Telangiectasia Mutated (ATM), the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 49 publications
4
39
0
1
Order By: Relevance
“…Our present data confirm an earlier observation that the induction of oxidative burst in leukocytes by PMA leads to distinct DNA damage response as evidenced by phosphorylation of histone H2AX on Ser-139 and activation of ATM through its phosphorylation on Ser-1981 (16). The induction of ROS in cells undergoing the oxidative burst was detected using the permeant H2DCFDA probe which becomes fluorescent upon oxidation (27).…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Our present data confirm an earlier observation that the induction of oxidative burst in leukocytes by PMA leads to distinct DNA damage response as evidenced by phosphorylation of histone H2AX on Ser-139 and activation of ATM through its phosphorylation on Ser-1981 (16). The induction of ROS in cells undergoing the oxidative burst was detected using the permeant H2DCFDA probe which becomes fluorescent upon oxidation (27).…”
Section: Discussionsupporting
confidence: 75%
“…Similar to prior studies, the extent of DNA damage was assessed by the cytometric analysis of H2AX phosphorylation and ATM activation (16,(22)(23)(24)(25), the early events of the DNA damage response (14,15,26). The data show significant attenuation of both H2AX phosphorylation and ATM activation by HA, consistent with the earlier evidence of the protective effect of this constituent of intercellular matrix on oxidative DNA damage in other cell systems (17)(18)(19)(20)(21)(22).…”
Section: Introductionsupporting
confidence: 74%
See 2 more Smart Citations
“…The extent of DNA damagewas assessed by measurement the induction of H2AX phosphorylation, the marker considered to report genotoxic changes in DNA molecule in chromatin [32][33][34][35][36][37][38][39]. Indeed in numerous studies phosphorylation of H2AX was shown to strongly correlate with other markers of DNA damage, such as assessed by single cell gel electrophoresis (comet assay), micronucleus assay or clonogenicity [33][34][35][36][37]48]. Our data show for the first time that exposure of cells to ICR-191 mutagen for 1 h was adequate to induce phosphorylation of H2AX.…”
Section: Protection Of Dna In Live Cellsmentioning
confidence: 99%